Zróżnicowanie wewnętrzne języka etnicznego a uniwersalne koncepcje kodów wspólnotowych. Od lingwistyki do semiotyki - Grzelak, Eliza (Studia Europaea Gnesnensia, 2014)
The author collected the most important findings concerning the internal diversification of the ethnic language (using Polish as an example) and, treating those concepts as a starting point, set out to present the contemporary universal linguistic, discursive and communicative communities. While stressing the high diversification of codes within the communities, the author returns to the rhetorical, adequately defined concept of three styles. In her description of the code of communicative community, the author draws a reference to the communal nature of rendering the image of the world and highlights its intersemiotic, supraethnic and universal character.